IDENTIFIKASI KERUSAKAN TEGAKAN SUNGKAI (Peronema canescens Jack) DI AREAL IUPHHK-HTI PT PRIMA MULTIBUANA KALIMANTAN SELATAN - Astrid Cahyani; Normela Rachmawati; Adistina Fitriani (Jurnal Sylva Scienteae, 2020)
The need for wood raw materials is increasing rapidly at this time, so it demands that local types of wood be utilized, such as sungkai (Peronema canescens Jack) which is one type of local plant. Sungkai that wants to be used and cultivated is certainly the best quality. Thus, it is important to know the health aspects and also damage to the sungkai stand that will be utilized. This riset aims to identify damage, find out the percentage of damage and determine the condition of the sungkai stand, with the form of data in the form of coding observations of stand physical conditions based on the standard of the Environmental Monitoring and Assessment Program (EMAP). Results of this riset is identification damage indicate such as burns, the presence of mushroom fruit bodies, weathering, holes (cavities), death due to illegal logging, and leaf damage. The highest percentage of damage is weathering reaching 43%. The lowest damage is open and dead wounds, the percentage is 1%. The condition of 166 sungkai stands that have been identified, is known that 51 sungkai trees are in the criteria of a healthy class. Sungkai stands which are categorized as light damage classes as many as 106 trees. The sungkai stand is in the category of moderate damage class of 5 trees. Criteria for class of severe damage only occur in one tree. There are three Sungkai trees with dead conditions due to illegal logging.Keywords: sungkai; EMAP; identification of damage; stand condition